The Role of Compensation, Digital Recruitment, Social Media, and Employer Branding in Attracting Generation Z to Careers in Jakarta - Mardiana Mardiana; Shandy Puspita (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the role of compensation, digital recruitment, social media, and employer branding in attracting Generation Z to pursue a career in Jakarta. The research method used is a quantitative approach with a purposive sampling technique. Data were collected through an online questionnaire distributed to 200 Generation Z respondents aged 18–28 years who live in Jakarta and are looking for work. Data analysis was conducted using multiple linear regression with the help of statistical software. The results show that partially compensation and digital recruitment have no effect on Generation Z's career interest. Meanwhile, social media and employer branding have a positive but insignificant effect on career interest. However, simultaneously compensation, digital recruitment, social media, and employer branding have a significant influence on Generation Z's career interest in Jakarta. These findings indicate that a company's strategy in attracting Generation Z cannot rely on a single factor, but requires an integrated approach that combines the use of social media and consistent strengthening of employer branding.